Components of a Change in the Balance of Trade - Worswick, G. D. N. (Review of Economic Studies, 1955)
Journal Article Components of a Change in the Balance of Trade Get access G. D. N. Worswick G. D. N. Worswick Oxford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 23, Issue 1, 1955, Pages 76–82, https://doi.org/10.2307/2296154 Published: 01 April 1955